The credit approval procedure : a brief analysis of the credit risk assessment system of Standard Chartered Bank and the level of satisfaction of the clients of local corporate segment - Audity, Athina Shaolin (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.